Hybridity and Cultural Dislocation in the Works of Amitav Ghosh - Ghosh, Isaac Ashish Kumar (Stallion Journal for Multidisciplinary Associated Research Studies, 2026)
The aim of this paper is to analyze the intersection of hybridity and cultural dislocation as the primary organizing themes of Amitav Ghosh’s fiction and non-fiction. It purports that Ghosh’s body of work depicts a radical reconstruction of historical and subjective constructions of humanity predicated on movement, encounters, and mixture, thus countering the totalizing abstractions of nation, culture, and civilization. This research attempts to identify how Ghosh approaches hybridity in his major novels, The Shadow Lines (1988), The Calcutta Chromosome (1995), The Glass Palace (2000), The Hungry Tide (2004), and the Ibis trilogy (2008-2015), as not a postmodern condition but one that is historical and ecological. Also, this research attempts to identify this overwhelming sense of dislocation that is often experienced as painful but also generative of new forms of knowledge and solidarity. Ghosh’s historiographical technique demonstrates what it means to revitalize lost narratives, such as those of indentured labourers as well as subaltern historiography, to combat the mono-causal, Eurocentric ‘master narratives’ of history. From an ethical perspective, his works call for radical empathy and propose an approach to history from the vantage point of the displaced and non-human, thus subverting anthropocentric perspectives. Utilizing Bhabha’s framework, Ghosh portrays a world of ‘third spaces’ where cultural hybridization and translation subvert the foundational axes of modernity. His critique addresses not only the political imposition of borders and boundaries but also the fractures that exist in the realms of the separation of modern science from folklore, history from fiction, and human agency from the rest of the material world.